Chemotactic movement and zeta potential dominate Chlamydomonas microsphaera attachment and biocathode development. Issue 12 (25th May 2023) - Chen, Guowei; Hu, Zhen; Ebrahimi, Ali; Johnson, David R.; Wu, Fazhu; Sun, Yifei; Shen, Renhao; Liu, Li; Wang, Gang
ABSTRACT: Microalgal cell attaching and biofilm formation are critical in the application of microalgal biocathode, which severs as one of the hopeful candidates to an original cathode in bioelectrochemical systems. Many efforts have been put in biofilm formation and bioelectrochemical systems for years, but the predominant factors shaping microalgal biocathode formation are sketchy. We launched a pair of researches to investigate microalgal attachment and biofilm formation in the presence/absence of applied voltages using Chlamydomonas microsphaera as a model unicellular motile microalga. In this study, we presented how microalga attached and biofilm formed on a carbon felt surface without applied voltages and try to manifest the most important aspects in this process. Results showed that while nutrient sources did not directly regulate cell attachment onto the carbon felt, limited initial nutrient concentration nevertheless promoted cell attachment. Specifically, nutrient availability did not influence the early stage (20–60 min) of microalgal cell attachment but did significantly impact cell attachment during later stages (240–720 min). Further analysis revealed that nutrient availability-mediated chemotactic movements and zeta potential are crucial to facilitate the initial attachment and subsequent biofilm formation of C. microsphaera onto the surfaces, serving as an important factor controlling microalgal surface attachment. Our results demonstrate that nutrient availability is a dominant factor controlling microalgal surface attachment and subsequent biofilm formation processes. This study provides a mechanistic understanding of microalgal surface attachment and biofilm formation processes on carbon felts surfaces in the absence of applied voltages. GRAPHICAL ABSTRACT: UF0001